A questão ambiental a partir de uma constituição sócio-histórica no município de Mata - RS - Hartmann, Renata de Baco (2016)
The dissertation here presented will deal, in general, about how the discussion spaces, in relation to the environmental issue. The city, which is geographically located in the central region of Rio Grande do Sul, is a result of a series of historical events, that happen since the arrival of the Luso-portuguese colonizer (considered the city’s funding agent) passing through the interventions imposed by the other European immigrants, specially Germans and Italians. By the actions of these social actors, drift the modification of the picture, overall with the vegetal suppression in the margins of Toropi River, for the installation of rice farming, and in the highest altitude, where corn, tobacco and others are actually cultivated. It can still be stated that, the means in how the environmental issue has been faced by the present generations, derive from this interweaving relations man-man and man-nature. Nevertheless, the objective of this research is: a) to understand, through the history of the place, how was the construction of the social group spaces, regarding the environmental issue; b) to identify, in the scope of work, the spaces in which the group of agriculturists search for attend of their demands, with regard to environmental issues and compliance with the law. Methodologically we adopted the constructionist approach, considering that in this study the eminently social aspect of the environmental issue, it is equivalent to say that the interest lies in how these environmental issues have been conducted, and if this historical route (Interspersed with a wide range of cultural, economic, and political factors), was the sufficient to understand the environmental issue, in this community, as public questions. Moreover, as background, the environmental history has been used to draw a line space-time around the people and the picture of the study place. In front of these characteristics, a qualitative research with empirical basis was adopted. The data was collected through interviews, bibliographical research, documental and observation research. The main conclusions of the study refer directly to the fact that the groups analyzed do not express great concern around the environmental issues, most probably because of the historiography of the place, substantiated the valorization of the work and the usage of natural resources as inputs to the agricultural activities.